Time, will, and mental process - Brown, Jason W. (Boston, MA : Springer US, 1996)
In this volume, distinguished neurologist Jason W. Brown extends the microgenetic theory of the mind by offering a new approach to the problem of time and free will. Brown bases his work on a unitary process model of brain and behavior. He examines the problem of subjective time and free will, the experiential present, the nature of intentionality, and the creative properties of physical growth and mental process.
Change -- Asymmetry of Past and Future -- Privacy -- Will, Agency, and Constraint -- Autonomy and Agent Causation -- Intention -- Desire and Value -- Belief and Conviction -- Action -- Morphogenesis and Mental Process -- Emergence -- Process and Creation.
Elektronická reprodukce.
Keywords: neurovědy; neuropsychologie; kognitivní psychologie; neurosciences; neuropsychology; cognitive psychology; e-knihy online; e-books online